Increasing incidence of bullous pemphigoid in Northern Finland: a retrospective database study in Oulu University Hospital. (19th October 2014) - Försti, A.‐K.; Jokelainen, J.; Timonen, M.; Tasanen, K.
Summary Background Bullous pemphigoid (BP) is an autoimmune blistering skin disease of elderly people. Some studies have suggested that the incidence of BP has increased, but the diagnostic accuracy and methodology of studies have varied considerably. Objectives To examine the incidence of BP in Northern Finland, and whether the incidence has changed over time. Methods This was a retrospective database study of all BP cases diagnosed in the Oulu University Hospital, Finland between 1985 and 2009. The diagnostic criteria were clinical features characteristic of BP (all patients) and positive direct or indirect immunofluorescence in the skin biopsy. The age‐standardized incidences were calculated by the direct standardization method. Incidence rate ratios (IRR) were estimated by the Poisson regression model. To derive adjusted IRRs, age and sex were used as potential confounding factors. Results The crude incidence of BP was 17 per 1 million person‐years [95% confidence interval (CI) 15–20] between 1985 and 2009. Using the general European population as a reference, the age‐standardized incidence was 14 per 1 million person‐years (95% CI 12–17). The incidence of BP increased 1·8‐fold (IRR 1·8, 95% CI 1·3–2·6; P < 0·001) in 2005–09 compared with the mean incidence of BP between 1985 and 2004, but after the adjustment for age and sex the increase was 1·4‐fold (IRR 1·4, 95% CI 1·0–2·0; P = 0·043). Conclusions This is the first study with immunohistologically verified BP diagnoses that reports the increase in the incidence of BP in age‐ and sex‐adjusted populations.